2011
DOI: 10.1021/ma201568h
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Initial Uncontrolled Polymerization and Its Suppression in the Copper(0)-Mediated Living Radical Polymerization of Methyl Acrylate in a Nonpolar Solvent

Abstract: We report the controlled polymerization of methyl acrylate in the presence of elemental copper at room temperature in a nonpolar solvent. As in single electron transfer (SET) living radical polymerization with nonactivated Cu(0), uncontrolled polymerization is observed early in the reaction. In the absence of marked disproportionation of copper(I) in our system, we propose that copper(0) is oxidized to copper(I) while activating the initiator, which triggers uncontrolled polymerization. Copper(I) then reacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 58 publications
2
69
1
Order By: Relevance
“…: the rates of comproportionation (k comp ) and disproportionation (k disp ) (in SET-LRP, disproportionation dominates; in SARA ATRP the equilibrium favors comproportionation); the rates of activation by copper(0) (k a0 ) and copper(I) (k a1 ) (in SET-LRP, all activation occurs by reaction with copper(0)); and the rate of bimolecular termination (zero or negligible in SET-LRP). The measurement of the rates of these elementary reactions has been a significant focus of our (19)(20)(21) and other groups' (22)(23)(24)(25) work in this field.…”
Section: Scheme 1 Reactions Of Copper Metal In Atom Transfer Radicalmentioning
confidence: 99%
See 3 more Smart Citations
“…: the rates of comproportionation (k comp ) and disproportionation (k disp ) (in SET-LRP, disproportionation dominates; in SARA ATRP the equilibrium favors comproportionation); the rates of activation by copper(0) (k a0 ) and copper(I) (k a1 ) (in SET-LRP, all activation occurs by reaction with copper(0)); and the rate of bimolecular termination (zero or negligible in SET-LRP). The measurement of the rates of these elementary reactions has been a significant focus of our (19)(20)(21) and other groups' (22)(23)(24)(25) work in this field.…”
Section: Scheme 1 Reactions Of Copper Metal In Atom Transfer Radicalmentioning
confidence: 99%
“…Thus performing polymerization in the presence of copper(0) in toluene (19,26,27) is a useful model for SET-LRP or SARA ATRP reactions in solvents that favor disproportionation or comproportionation, as equilibration between copper species can be neglected, leading to the simplified mechanism shown in Scheme 3. It is immediately apparent from Scheme 3 that the reaction involves net consumption of copper(0) and generation of dead polymer -indeed it could be summarized as:…”
Section: Polymerization In Noncomproportionating Nondisproportionatimentioning
confidence: 99%
See 2 more Smart Citations
“…Matyjaszewski has proposed that SET‐LRP cannot occur via an OSET process, but rather SET‐LRP should be thought of as a form of ARGET‐ATRP, with the copper(0) metal reducing copper(II) deactivator into copper(I) species, whereas at the same time acting as a supplemental activator (SARA‐ATRP). Other research groups have shown that in nonpolar solvents, copper(0) can act as an activator through reactions with the alkyl halide initiator to generate a secondary radical source in an analogous system to ICAR‐ATRP …”
Section: Copper(0)‐mediated Crpmentioning
confidence: 99%